2020
DOI: 10.1155/2020/2431705
|View full text |Cite
|
Sign up to set email alerts
|

CXCL14 Overexpression Attenuates Sepsis-Associated Acute Kidney Injury by Inhibiting Proinflammatory Cytokine Production

Abstract: CXCL14 is a relatively novel chemokine with a wide spectrum of biological activities. The present study was designed to investigate whether CXCL14 overexpression attenuates sepsis-associated acute kidney injury (AKI) in mice. Sepsis model has been established by cecal ligation and puncture (CLP). CLP induced AKI in mice as assessed by increased renal neutrophil gelatinase-associated lipocalin (NGAL) expression and serum creatinine levels. We found that renal CXCL14 expression in the kidney was significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…This activation may lead to favorable or unfavorable gene expression changes for host cells and contribute to ARDS shown in some COVID-19 patients [ 56 ]. In addition to the pathways, inflammatory chemokines, such as C–X–C motif chemokine ligand 1 ( CXCL1 ), CXCL2 , CXCL3 , CXCL5 and CXCL6 , were significantly upregulated as previously reported [ 24 ], while CXCL14 with anti-inflammatory activity [ 57 ] was substantially downregulated ( Table S1 ). Several interleukin genes, including interleukin 1 alpha ( IL1A ), IL1B , IL32 , IL36G , IL6 and IL8 , were also upregulated in SARS-CoV-2-infected NHBE cells along with SOCS3, which has been shown to function as an IL-6 inhibitor [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 75%
“…This activation may lead to favorable or unfavorable gene expression changes for host cells and contribute to ARDS shown in some COVID-19 patients [ 56 ]. In addition to the pathways, inflammatory chemokines, such as C–X–C motif chemokine ligand 1 ( CXCL1 ), CXCL2 , CXCL3 , CXCL5 and CXCL6 , were significantly upregulated as previously reported [ 24 ], while CXCL14 with anti-inflammatory activity [ 57 ] was substantially downregulated ( Table S1 ). Several interleukin genes, including interleukin 1 alpha ( IL1A ), IL1B , IL32 , IL36G , IL6 and IL8 , were also upregulated in SARS-CoV-2-infected NHBE cells along with SOCS3, which has been shown to function as an IL-6 inhibitor [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 75%
“…These findings are in line with our transcriptome data showing that Retnla, a hallmark of alternatively activated M2 macrophages, was significantly downregulated in cKO mice [ 44 ]. Moreover, CXCL14, a chemokine that has been recently described as inhibiting M1 macrophage polarization but increasing M2 polarization, was markedly reduced in SM-CXCL12 −/− mice, supporting a proinflammatory state [ 45 ]. Previous studies have shown that cardiac M2-like macrophages exhibit tremendous anti-inflammatory and tissue repair capabilities, whereas M1-like macrophages rather reflect a pro-inflammatory status after MI [ 44 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL14/BRAK promotes chemotaxis of immature dendritic cells, neutrophils, monocytes, activated human NK cells, and others [137]. CXCL14 has been detected in kidney specimens, however, it has not been extensively investigated, except for a study where CXCL14 overexpression mitigates sepsis-induced AKI, probably through the regulation of the M1/M2 macrophage ratio and the downregulation of cytokine production [138].…”
Section: Discussionmentioning
confidence: 99%